Cladocera of Hainan Island, China - Sinev, Artem Y.; Gu, Yangliang; Han, Bo-Ping (Zootaxa, 2015)
The cladoceran fauna of Hainan Island (China) was investigated. Samples were collected in January 2013 and in April 2014 from over hundred water bodies, including large and small reservoirs, ponds and pools, rivers, streams, and paddy fields. There are no large natural lakes on the island. We found 53 species of Cladocera: 9 species of Sididae; 5 Daphniidae; 2 Moinidae; 2 Macrothricidae; 2 Ilyocryptidae; 3 Bosminidae; and 30 Chydoridae. Planktonic communities were dominated by Diaphanosoma dubium Manuilova, 1964, D. excisum Sars, 1885, D. sarsi Richard, 1894, Moina micrura Kurz, 1874 and Bosminopsis deitersi (Richard, 1895). Six Chydoridae species are first records for China. The fauna consists mostly of Oriental and Pantropical species, but, also includes non-tropical Palaearctic species and East Asian endemics. For these species, Hainan Island is the southernmost record. The number of species is rather small, compared to adjacent areas. This may reflect a low intensity of sampling, but more likely a lack of natural lakes. Communities in reservoirs suffer from water level fluctuations, and the absence of permanent macrophyte stands, a preferred habitat of littoral cladocera.